Perfect competition, market power, and contestability - Oliver Budzinski; Annika Stöhr (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2024)
The model of perfect competition is one of the most famous, most important, and most misunderstood concepts in economics. Rather than aiming to be a full-blown model of real-world competitive markets, the perfect competition model isolates the decentralized coordination mechanism inherent in all competitive markets. Coordinating supply and demand is not the only feature of market competition, but it plays a central role regarding to its virtues, and understanding the working mechanism of this coordination is valuable for economic thinking and economic theory. However, the implications of the perfect competition model for competition law and policy are limited. Market power is a multifaceted phenomenon that consists of several distinguishable types. This contribution explains absolute market power (single-firm monopoly and dominance), collective market power, relative market power, and systemic market power. Due to the possibility of merit-driven paths to market power positions (especially disruptive innovations), market power is difficult to prohibit - despite its welfare-reducing effects within the affected markets (anticompetitive effects) and in other parts of the economy and society (rent-seeking, lobbying, distributional issues). Therefore, competition policy usually focuses on preventing non-merit paths to market power (merger control) and on combating the (anticompetitive) abuse of market power. Contestability refers to the openness of markets. More specifically, it is the ability of companies to overcome barriers to entry and exit as well as to expansion on markets. While the original economic theory of contestability defines very strict conditions for perfectly contestable markets, antitrust has employed the term contestability in broader and in varying ways, emphasizing the role of potential competition and potential market entries to discipline the behavior of powerful incumbents on monopoly or dominance markets. Recently, contestability is rising to new prominence as a major goal of the European regulation of digital ecosystems.
Keywords: A10; A20; B10; B20; D00; K21; L12; L13; L40; 330; perfect competition; atomistic competition; coordination of supply and demand; market power; monopoly; market concentration; dominance; digital ecosystems; price setting; economic power; contestability; entry barriers; exit barriers; potential competition; open markets; Digital Markets Act (EU)